2022
DOI: 10.1155/2022/1498293
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Worsening of Bone Loss in Patients Newly Diagnosed with Inflammatory Bowel Disease

Abstract: Background. Bone loss is common in patients with inflammatory bowel disease (IBD). The aim of the present study was to determine the prevalence of metabolic bone disease in patients newly diagnosed with IBD and to identify the risk factors for bone loss over time. Methods. We performed a retrospective, both cross-sectional and longitudinal, study to extract the risk factors of bone loss (including osteopenia and osteoporosis) in patients newly diagnosed with IBD, using dual-energy X-ray absorptiometry (DXA). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
5
1
1
Order By: Relevance
“…Even though the impact of BMI is a less direct indicator of disease severity, it still has a significant impact on low BMD 18 . Different findings have been reported in the previous studies regarding the impact of disease duration on bone loss 17,20 . In the current study, though univariate analysis showed that a disease duration of 6 months and longer was related to low BMD, this was not shown in the multivariate analysis ( P = 0.066; T‐score).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Even though the impact of BMI is a less direct indicator of disease severity, it still has a significant impact on low BMD 18 . Different findings have been reported in the previous studies regarding the impact of disease duration on bone loss 17,20 . In the current study, though univariate analysis showed that a disease duration of 6 months and longer was related to low BMD, this was not shown in the multivariate analysis ( P = 0.066; T‐score).…”
Section: Discussioncontrasting
confidence: 87%
“…A study on a Chinese population (n = 5593) has revealed that male patients aged 40–50 years had an osteoporosis rate of 0.4% at the femoral neck and 2.6% at the lumbar spine 15 . The prevalence of osteoporosis in our IBD patients was higher compared with that reported in the general Chinese population, 16 but is comparable to that previously reported 17 . The prevalence of low BMD in patients with IBD at the initial diagnosis may be low, which may increase during the follow‐up period according to the American Gastroenterological Association guideline.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Lactobacillus can reduce body weight and alleviate fat accumulation in mice fed a high-fat diet ( Wang et al, 2020 ). For osteoporosis patients, increasing BMI was identified as a protective factor for bone loss ( Wang Y et al, 2022 ; Yin et al, 2022 ). The results from a large cohort survey showed that the mean rate of fragility fracture was significantly increased in the underweight group compared with the obese and normal weight groups in postmenopausal women ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…24 Long-term Cs use reduces BMD and has been involved with reduced bone density in patients with IBD, although some studies did not find such a connection. 25 In a study of 166 patients with IBD, Abraham et al 26 showed that Cs use more than doubled the risk of low BMD (OR = 2.4 (1.5-3.6), P = .001). However, other studies did not reveal a clear association between low BMD and Cs use.…”
Section: Discussionmentioning
confidence: 99%